2020
DOI: 10.1042/bsr20200164
|View full text |Cite
|
Sign up to set email alerts
|

DHA inhibits Gremlin-1-induced epithelial-to-mesenchymal transition via ERK suppression in human breast cancer cells

Abstract: Docosahexaenoic acid (DHA) is an omega-3 fatty acid abundant in fish oils. It is known to have an inhibitory effect on various diseases such as inflammation, diabetes, and cancer. Epithelial-to-mesenchymal transition (EMT) is a process that epithelial cells gain migratory property to become mesenchymal cells involved in wound healing, organ fibrosis, and cancer progression. Gremlin-1 (GREM1) is a bone morphogenetic protein antagonist known to play a role in EMT. However, the role of GREM1 in the induction of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…In this study, we used bioinformatics analysis methods to construct a full-genome expression profile of BC metastasis samples combined with an EMT-related gene weighted co-expression network and BC prognosis evaluation model to provide the basis and reference for calculating prognostic risk values for BC patients. Several studies have confirmed that genes, such as BMP-2, BMPR2, GREM1, CEMIP, HGF, ITGA5, ITGB1, MCAM , and TGFBR1 , are closely related to the EMT process in BC cells, which is also consistent with our research results [6 , 7 , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, we used bioinformatics analysis methods to construct a full-genome expression profile of BC metastasis samples combined with an EMT-related gene weighted co-expression network and BC prognosis evaluation model to provide the basis and reference for calculating prognostic risk values for BC patients. Several studies have confirmed that genes, such as BMP-2, BMPR2, GREM1, CEMIP, HGF, ITGA5, ITGB1, MCAM , and TGFBR1 , are closely related to the EMT process in BC cells, which is also consistent with our research results [6 , 7 , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ].…”
Section: Discussionsupporting
confidence: 92%
“…With in-depth studies of BC, people gradually realized the importance of EMT in the occurrence and metastasis [6 , 7 , [10] , [11] , [12] ]. Tumor cells often need to lose their epithelial-like phenotypic characteristics, such as polarity and intercellular contact via EMT to invade normal tissues and metastasize [6 , 7 , [10] , [11] , [12] , [13] , [14] ]. The metastasis of BC epithelial cells, the development of breast ductal carcinomas in situ into invasive BC, the poor efficacy of BC treatment, and the resistance of patients to chemotherapy drugs are all closely related to the EMT process [6 , 7 , [10] , [11] , [12] , [13] , [14] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activating the EMT and progressing through the metastatic process is a key determinant of BC prognosis as the median survival rate for metastatic TNBC is ~10–13 mo ( 5 ). In addition to proliferation, DHA was shown to inhibit migration ( 44 , 49 , 51 , 52 ) and invasion ( 41 , 44 , 50 ) of TNBC in culture. Mouse experiments using the tail vein injection model in Fat-1 mice, which produce higher amounts of endogenous ω-3 essential fatty acids, also suggested a potential anti-metastatic effect ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor (TGF)β is a cytokine that promotes EMT of epithelial cells ( 82 ). In two different TNBC cell lines, MDA-MB-435 and Hs578T, DHA (25 μM) suppressed transforming growth factor (TGF)β-mediated increases in the expression of the EMT mediators gremlin (GREM)1, N-cadherin, vimentin, and Slug ( 49 ). Stimulation of MDA-MB-435 cells with TGFβ had a pro-migratory effect in wound healing assays that was attenuated by either GREM1 silencing or treatment with DHA.…”
Section: Fish Oil and Tnbc: Reviewmentioning
confidence: 99%